Parents' Perspective of Quality of Life of Retinoblastoma Survivors. Issue 7 (1st April 2016) - Batra, Atul; Kain, Raman; Kumari, Mamta; Paul, Reeja; Dhawan, Deepa; Bakhshi, Sameer
Abstract : Health‐related quality of life (HRQOL) in retinoblastoma survivors was assessed using parent proxy report of PedsQL TM 4.0 generic core scale. One hundred twenty‐two parents of retinoblastoma survivors filled the questionnaire satisfactorily. This was compared with parent‐reported HRQOL of 50 siblings. The median age of survivors was 98 (range, 60–247) months and male:female ratio was 2:1. The overall parent‐reported HRQOL was significantly worse in survivors as compared to controls (74.4 ± 8.5 vs. 85.1 ± 4.6, P < 0.001). All health domains were significantly affected when compared with controls. None of the baseline and treatment‐related factors predicted HRQOL.